Treatment of lumbar intervertebral disc herniation - a review of the latest therapeutic methods - Klocek, Konrad; Kostecki, Bartosz; Hajduk, Aleksandra; Mrozek, Łukasz; Jurek, Aleksander; Zwolski, Maciej; Szumlas, Zuzanna; Puchalski, Krzysztof (Journal of Education, Health and Sport, 2023)
Introduction and purpose: The aim of this study is to provide a comprehensive description of intervertebral disc herniation, with a focus on the lumbar spine, including the current conservative and modern surgical treatment options such as minimally invasive procedures. State of Knowledge: Spinal pain is a prevalent cause of disability in developed countries, with an increasing number of people affected by this condition. Intervertebral disc herniation resulting from degenerative changes is a common pathology, particularly in the lumbar and cervical spine. This condition involves the protrusion of the nucleus pulposus, which exerts pressure on the spinal roots, causing irritation. While the prognosis for herniated nucleus pulposus is usually positive and many patients can undergo conservative treatment, some may require a surgery. Due to advancements in technology, the current goal is to minimize tissue trauma during hernia repair procedures. Conclusions: Due to advances in treatment of lumbar intervertebral disc herniation, patients can achieve better clinical outcomes and improved quality of life. Conservative treatment should be considered as the first line treatment in a majority of cases. Surgery is usually a last resort when conservative treatment proves insufficient. No surgical method seems to be unequivocally superior to the others, so its choice is tailored to the individual patient’s needs and depends on the surgeon’s preferences and experience. Recent advances in endoscopic spine surgery are providing new insights into disc surgery and pain management strategies.